2012
DOI: 10.1002/asia.201200976
|View full text |Cite
|
Sign up to set email alerts
|

3,14‐Bis(p‐nitrophenyl)‐17,17‐dipentyltetrabenzo[a,c,g,i]‐fluorene: A New Fluorophore Displaying Both Remarkable Solvatochromism and Crystalline‐Induced Emission

Abstract: A series of 17,17-dialkyl-3,14-diaryltetrabenzofluorenes were efficiently prepared by using Suzuki-Miyaura cross-coupling reactions of the corresponding 3,14-dibromo derivatives. Studies of the unique fluorescence properties of these compounds showed that they display intense blue to yellow fluorescence with high quantum yields in the solution state and blue to orange fluorescence with moderate quantum yields in the solid state. In addition, the fluorescence wavelength of the bis(p-nitrophenyl) derivative is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In contrast to 23 , dye 24 85 fluoresces predominately in solvents of low polarity, reaching the highest value of Φ f in toluene (0.37) (Fig. 13 and 14).…”
Section: Suppressing Intersystem Crossing In Moderately Polar Solventsmentioning
confidence: 94%
“…In contrast to 23 , dye 24 85 fluoresces predominately in solvents of low polarity, reaching the highest value of Φ f in toluene (0.37) (Fig. 13 and 14).…”
Section: Suppressing Intersystem Crossing In Moderately Polar Solventsmentioning
confidence: 94%
“…Studies of disubstituted benzenes 29 , bis-ethynobenzenes 30 , disubstituted naphthalenes 31 , and fused nitro-fluorenes 32,33 demonstrate these design principles for organic branched fluorescent nitro-aromatics. In these examples, an increase in solvent polarity increases the fluorescence efficiency, which indicates that radiative deactivation occurs from states with a pronounced CT character 8,34 .…”
mentioning
confidence: 90%
“…Xu et al reported a new D-p-A system OZA-SO, which also displayed the AIE phenomenon by the restriction of ICT. 29 Besides, several materials with ICT and AIE properties were reported, for example, tetrabenzofluorene derivatives, 30 dicarbazolyl triphenylethylene derivatives. 31 The investigations on the D-p-A molecules may help to reveal the intrinsic process of the fluorescence enhancement and spectral shifts in their molecular aggregates.…”
Section: Introductionmentioning
confidence: 99%